Adoption concerns for the deployment of interactive public displays at schools - Lencastre, José Alberto (2014)
JuxtaLearn is a research project focused on ‘performance’ as a means of provoking students’ understanding of science and technology through the creation and sharing of educational videos. As the videos will be shared in public displays, the Portuguese research team developed three workshops with twelve teachers from a Portuguese Secondary School representing different school departments and sharing organizational responsibilities. The aim was to generate scenarios of possible features and interaction for the curricular integration of the technological device. Our findings suggest that teachers are not motivated to use, on their own, technologies in the classroom, but receptive to new and challenging technologies when properly stimulated. They were able to generate scenarios that take advantage of the possibilities offered by digital public displays to stimulate learning processes. However, there are pedagogical, organizational and ethical concerns in the management and control of content that need to be resolved before they feel confortable to deal with change and technological innovation.